Struggles In (Elderly) Care : A Feminist View - Dahl, Hanne Marlene (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book provides a critical engagement with the intensified struggles to be found within elderly care provision. Various social and political processes, including the forces of globalisation and the de-gendering of care, have changed how we might understand this national and global political concern. Emerging discourses such as neoliberalism have also reframed elderly care to increase existing tensions at the individual, national, and transnational level. Dahl argues that in order to grasp these new realities of care we need a new analytical framework that redirects us to new sites of contestation. Dahl approaches these issues from a post-structuralist and radical feminist position, while drawing from feminist sociology, feminist political science, nursing philosophy and feminist history. In particular, Struggles In (Elderly) Care highlights how the predominantly feminist theorization of care has been dominated by a sociological bias that could be improved using insights from political science concerning concepts of power and struggle, and the importance of the state and governance. This book will be of interest to researchers in sociology, gerontology, nursing, and feminist studies.